Spillover effects from the Volkswagen emissions scandal: An analysis of stock and corporate bond markets - Florian Barth; Christian Eckert; Nadine Gatzert; Hendrik Scholz (Schmalenbach Journal of Business Research (SBUR), 2022)
This study examines spillover effects following Volkswagen's admission of emissions cheating. We first estimate initial operational losses of 8.45% of Volkswagen's equity market capitalization on the date before the announcement, reputational losses up to five times these losses, and significant negative shocks to its stocks and bonds. Analyzing spillover effects from this shock beyond the usually only measured losses in equity value, we find significant negative net spillover effects to European competitors and suppliers in both stock and bond markets. Studying the economic effects in more detail, we show that Volkswagen's total losses of 27.4 billion euros in terms of changes in equity market values over the first five event days are almost entirely composed of abnormal losses. Furthermore, competitors (suppliers) overall suffered 18.3 (12.6) billion euros of abnormal losses during this time, with 60% (69%) of the firms exhibiting negative changes, especially European competitors and suppliers connected to Volkswagen. These figures are further increased by negative bond market value changes. Overall, our results strongly emphasize that neglecting debt holders losses can lead to an underestimation of such events.
Keywords: 650; Event study; Operational risk; Spillover effects; Volkswagen emissions scandal